Penyuluhan pemilihan dan penggunaan kosmetik yang aman tanpa bahan kimia berbahaya terhadap remaja - Mariyani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2023)
Cosmetics are used with the aim of improving and maintaining beauty to support the appearance of the primary needs of today, especially among adolescents. The development of cosmetic trends is currently a threat because there are some manufacturers who add substances that are prohibited in the addition of cosmetics in order to get instant results without thinking about the effect, so that assistance is made so that people understand about the selection and use of Safe Cosmetics and the impact of using cosmetics with harmful chemicals. This activity uses counseling methods and media leaflets, thereby increasing public understanding of cosmetics. It is expected that the youth of Lampo Village, Donggala Regency have knowledge and wisdom in choosing and using cosmetics Keywords—cosmetics, service, community, education